Electromagnetic Antenna Cloaking with Metamaterial Structures (Global Journals of Research in Engineering, 2022)
Electromagnetic (EM) cloaks, based on spatial transformations, can potentially be utilized as shielding devices for antennas in close proximity with multiple antenna arrangements as well as highly scattering environments. In these environments each antenna can be enclosed in a cloak that is designed to be shield at the transmitting frequencies of the neighboring antennas, but assumes free space values for the shielded antenna so it can radiate unimpeded. Perfect EM cloaking is, however, difficult owing to the anisotropic, inhomogeneous material parameters of the cloak. The physical embodiment of such structures, as well as numerical calculations, is exceedingly difficult, if not impossible, for realistic 3-D structures. To overcome these immense issues, this research utilizes dispersive media (Drude or Lorentz models) that can minimize some of the problems (anisotropic, inhomogeneous material parameters) associated with #x201C;true#x201D; cloaks, but can yield similar cloaking properties. The resulting cloak is frequency dependent which cloaks at a specific frequency and is transparent at other frequencies. The resulting medium is isotropic and homogeneous.